Development of Obsessive-Compulsive Symptoms Following Abrupt Discontinuation of Venlafaxine - Gahr, Maximilian; Hiemke, Christoph; Kölle, Markus Alexander (Frontiers in Psychiatry, 2020)
Withdrawal symptoms after discontinuation of antidepressants are common and have long been known. Typical symptoms after dose reduction or discontinuation of antidepressants are dizziness, drowsiness, headache, flu-like symptoms, hyperarousal, imbalance, insomnia, irritability, and nausea. Rebound, relapse or recurrence associated with the underlying mental disorder may also occur. The occurrence of obsessive compulsive symptoms (OCS) following abrupt discontinuation of antidepressants have not yet been reported. Here we report the development of OCS (obsessional suicidal thoughts) in a patient with major depressive disorder and absence of a previous obsessive-compulsive disorder following abrupt discontinuation of venlafaxine. Treatment with escitalopram facilitated remission of OCS. We discuss a possible causal link between abrupt discontinuation of venlafaxine and development of OCS under consideration of pathophysiologic aspects regarding obsessive compulsive disorders, the chronological sequence of symptoms in the present case and pharmacodynamic and -kinetic aspects. Our case report suggests the possibility of the occurrence of obsessive-compulsive symptoms following abrupt discontinuation of venlafaxine.